Parathyroid Hormone Promotes Human Umbilical Vein Endothelial Cell Migration and Proliferation Through Orai1-Mediated Calcium Signaling - Wang, Shuhao; Xu, Lijie; Wu, Yv; Shen, Hailong; Lin, Zhangying; Fang, Yang; Zhang, Lesha; Shen, Bing; Liu, Yehai; Wu, Kaile (Frontiers in Cardiovascular Medicine, 2022)
Parathyroid hormone is the main endocrine regulator of extracellular calcium and phosphorus levels. Secondary hyperparathyroidism–induced endothelial dysfunction may be related to calcium homeostasis disorders. Here, we investigated the effects of parathyroid hormone on human umbilical vein endothelial cells (HUVECs) and characterized the involvement of store-operated Ca2+ entry (SOCE) and the nuclear factor of activated T cells (NFAT) signaling pathway. We used immunoblot experiments to find that parathyroid hormone significantly enhanced the expression of the Orai1 channel, a type of channel mediating SOCE, SOCE activity, and Orai1-mediated proliferation of HUVECs but did not increase Orai2 and Orai3. RNA-seq was utilized to identify 1,655 differentially expressed genes (823 upregulated and 832 downregulated) in parathyroid hormone–treated HUVECs as well as enhanced focal adhesion signaling and expression levels of two key genes, namely, COL1A1 and NFATC1. Increased protein and mRNA expression levels of COL1A1 and NFATC1 were confirmed by immunoblotting and quantitative RT-PCR, respectively. Cytosol and nuclei fractionation experiments and immunofluorescence methods were used to show that parathyroid hormone treatment increased NFATC1 nuclear translocation, which was inhibited by a calcineurin inhibitor (CsA), a selective calmodulin antagonist (W7), an Orai channel inhibitor (BTP2), or Orai1 small interfering RNA (siRNA) transfection. Parathyroid hormone also increased COL1A1 expression, cell migration, and proliferation of HUVECs. The PTH-induced increase in HUVEC migration and proliferation were inhibited by CsA, W7, BTP2, or COL1A1 siRNA transfection. These findings indicated that PTH increased Orai1 expression and Orai1-mediated SOCE, causing the nuclear translocation of NFATC1 to increase COL1A1 expression and COL1A1-mediated HUVEC migration and proliferation. These results suggest potential key therapeutic targets of Orai1 and the downstream calmodulin/calcineurin/NFATC1/COL1A1 signaling pathway in parathyroid hormone–induced endothelial dysfunction and shed light on underlying mechanisms that may be altered to prevent or treat secondary hyperparathyroidism–associated cardiovascular disease.